The Impact of Accounting Earnings Quality using the Sustainability model (Persistence) in the performance of the Company An Applied Research In A Sample Of Joint Stock Banks Listed On The Iraq Stock Exchange - Thair K. Hameed; Wafaa Abd Al-Ameer Al-Dabbas (Journal of Madenat Alelem University College, 2021)
The research aims to measure the extent of the impact of Accounting Earnings quality in the firms performance for a sample of private commercial banks listed on the Iraq Stock Exchange. The research sample included (5) of the listed commercial banks that continue to issue their financial statements for the period from (2009-2018), namely (Ashur Bank, Credit Bank, Middle East Bank, Mosul Investment Bank, and Gulf Commercial Bank). The research relied on two main models for measurement. In three steps, the first step included measuring the Persistence (Earnings quality) by adopting the sustainability model (Kamarudin and Ismail, 2014), while the second step included measuring the firm’s performance through the modified Tobin’s Q scale based on the model (Doidge, Karolyi and Stulz’s, 2001) (30), while the third step focused on measuring the impact of Earnings quality (Persistence) as an independent variable in the main dependent variable represented by the firm’s performance (Tobin’s Q), using the simple linear regression analysis method. The research reached a number of conclusions, the most important of which are: - 1. The majority of Iraqi banks listed on the Iraq Stock Exchange in general are distinguished by Earnings quality through the model of (sustainability) the permanence of profits that was used for the period from 2009 to 2018, as the result of the study showed that the banks of the research sample are distinguished by the persistence (high earnings quality) It is also distinguished by its non-failure or bankruptcy in terms of financial performance and the percentage of profits achieved. 2. The existence of a significant statistical impact between the Persistence (Earnings quality) and the firm’s performance, as the results of the study showed that there is an effect and a direct relationship. The higher earnings quality, the higher firm’s performance. So the researcher recommends: 1. Working on adopting a sustainability model (Persistence) in measuring the Earnings quality in banks listed on the Iraq Stock Exchange. With the possibility of using other models of Earnings quality measures to reach the most efficient and optimal model in measuring the Earnings quality. The need for Iraqi banks to adopt models for financial performance to help them avoid financial failure and stumbling in performance, to show their strengths and weaknesses, so that the higher management can take appropriate decisions and overcome the expected risks. With not limited to using the financial indicators extracted from the bank’s accounting data in order to measure performance, as this must be extended to linking non-financial indicators that take into account the variables related to the company’s internal and external environment.